Ultrafast wafer-scale assembly of uniform and highly dense semiconducting carbon nanotube films for optoelectronics. (15th August 2020) - Su, Wei; Yang, Dehua; Cui, Jiaming; Wang, Futian; Wei, Xiaojun; Zhou, Weiya; Kataura, Hiromichi; Xie, Sishen; Liu, Huaping
Abstract: We report an innovative method for the fast preparation of wafer-scale uniform single-wall carbon nanotubes (SWCNT) films with controllable density by NaHCO3 tuning the interaction between amine-functionalized substrates and surfactant-dispersing SWCNTs in aqueous solution. With this technique, a 4-inch SWCNT film with a linear density of ∼30 tubes/μm can be achieved in 1 s, and over 60 tubes/μm within 30 s using a high-concentration SWCNT solution. The SWCNT density changes by less than 8% over a 4-inch area. The electrical uniformity of the as-prepared wafer-scale single-chirality SWCNT film was demonstrated to be within 10.8% for subthreshold swing and 12% for carrier mobility and 13.5% for their on-current, which is the most uniform SWCNT films reported so far fabricated from the surfactant-dispersed SWCNT solution. Further, the photodetectors made by the uniform semiconducting SWCNT films exhibit excellent cascading ability, which linearly amplify the output photovoltages and could produce a photovoltage responsivity of 2.5 × 10 6  V/W. When three-stage cascading photodetectors are used as optical gate to establish an integrated photoelectric system, a 20-mW/cm 2 light illumination produces the current responsivity of 147.3 A/W under a source/drain voltage of −0.1 V. Our present technique lays an important foundation for their applications in integrated circuits. Graphical abstract: Image 1